Annual World Bank Conference on Development Economics, 2001/2002 - Bank Conference on Development Economics Washington, D.C. 2001; Stern, N. H.; Pleskovic, Boris (Washington, DC New York: World Bank: Oxford University Press, 2002)
"The 13th annual conference, held in May 2001, concentrated on the current thinking in development policy and the implications for the global economy with a particular focus on the two important and controversial themes of globalization and health."
Includes bibliographical references.
Keywords: BUSINESS & ECONOMICS -- -- Urban & Regional; Developing countries -- -- Economic policy; Developing countries -- -- Economic conditions; Developing countries -- -- Politics and government; Electronic books